Evaluation of adipokines concentrations in plasma, peritoneal, and endometrioma fluids in women operated on for ovarian endometriosis - Wójtowicz, Mariusz; Zdun, Dariusz; Owczarek, Aleksander Jerzy; Skrzypulec-Plinta, Violetta; Olszanecka-Glinianowicz, Magdalena (Frontiers in Endocrinology, 2023)
Introduction Some studies indicate the role of selected adipokines in the development of endometriosis. However, a comprehensive assessment of plasma, peritoneal, and endometrioma fluids adipokines concentrations in women with ovarian endometriosis has not yet been performed. Therefore, this study aimed to analyze plasma, peritoneal, and endometrioma fluids selected adipokines concentrations in women operated on for ovarian endometriosis. Materials and methods A cross-sectional cohort study involved 56 women operated on for ovarian endometriosis. Body mass, height, and waist circumference were measured, and BMI was calculated. Plasma, peritoneal, and endometrioma fluids adiponectin, leptin, omentin resistin, RBP4, and visfatin/NAMPT were determined by ELISA. Results The highest plasma levels of adiponectin, leptin, omentin, and RBP4 than in the endometrioma and peritoneal fluids were found, while levels of resistin and visfatin/NAMPT were significantly higher in endometrioma fluid than in plasma and peritoneal fluid. In addition, levels of visfatin/NAMPT were significantly higher in peritoneal fluid than in plasma. There were also positive correlations between leptin, RBP4, and adiponectin levels in endometrioma and peritoneal fluids (ρ = 0.28; p < 0.05; ρ = 0.31; p < 0.05; ρ= 0.32; p < 0.05, respectively). There were no associations between adipokines levels in plasma, endometrioma, and peritoneal fluids and endometriosis stage. Conclusion Our results show that visfatin/NAMPT and resistin may be locally secreted in endometrioma related to inflammation regardless of the stage of endometriosis.